The ceiling outside : the science and experience of the disrupted mind - Arikha, Noga (London: Basic Books, 2022)
"A diabetic woman awakens from a coma having forgotten the last ten years of her life. A Haitian immigrant has nightmares that begin bleeding into his waking hours. A retired teacher loses the use of her right hand due to pain of no known origin. Noga Arikha began studying these patients and their confounding symptoms in order to explore how our physical experiences inform our identities. Soon after she initiated her work, the question took on unexpected urgency as Arikha's own mother began to show signs of Alzheimer's disease. In The Ceiling Outside, Arikha recounts this life-changing experience and grapples with the unbreakable links between our bodies and our sense of self. Weaving together stories of her subjects' troubles and her mother's decline, Arikha searches for some meaning in the science she has set out to study. The result is an unforgettable journey across the ever-shifting boundaries between ourselves and each other."----
The double mirror -- The old campus -- The lost years -- Haunted -- Appearances -- Guilty as charged -- Hold my hand -- Impostors -- The affront -- Coda.
"First published in 2022 in Great Britain by Basic Books London"--Title page verso.
Includes bibliographical references (pages 213-282) and index.
Keywords: Arikha, Noga -- Family; Mind and body; Self (Philosophy); Dementia